2022
DOI: 10.1155/2022/7267937
|View full text |Cite
|
Sign up to set email alerts
|

Association between Cystatin C and Cardiac Function in Acute Myocardial Infarction Patients: A Real-World Analysis

Abstract: Background. Acute myocardial infarction (AMI), as well as its long-term and short-term complications, is known to present with high morbidity and mortality. Cardiac function deterioration and ventricular remodelling after AMI are known to be correlated to worse long-term outcomes. However, the underlying mechanism remains elusive and there is a shortage of serum prediction markers. This study investigates the relationship between in-hospital Cystatin C (CysC) and cardiac function and subsequent prognosis among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Also, our study revealed statistically significant negative correlation between Cystatin C and LVEF with p-value=0.000. Recently, Lou et al, presented Cystatin C levels at admission as a biomarker of cardiac function and they showed a negative relationship with EF with p-value <0.001 [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Also, our study revealed statistically significant negative correlation between Cystatin C and LVEF with p-value=0.000. Recently, Lou et al, presented Cystatin C levels at admission as a biomarker of cardiac function and they showed a negative relationship with EF with p-value <0.001 [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this biomarker is a useful predictor for no-reflow events in STEMI patients treated with pPCI [ 109 ]. Recently, Lou et al [ 110 ] presented cysC levels at admission as a biomarker of cardiac function, and they showed a negative relationship with the ejection fraction value ( p < 0.0001) and functioned as a predictor for MACEs, cardiovascular mortality and all-cause mortality in AMI patients within 4 years of follow-up. In addition, elevated levels of cysC measured at any stage within the first year after an ACS positively correlated with the composite endpoint (cardiac mortality, non-fatal AMI and unplanned coronary revascularization) ( p = 0.006).…”
Section: Resultsmentioning
confidence: 99%
“…18 A significant association exists between elevated Cys C and the risk of cardiovascular events or mortality in heterogeneous populations with normal renal function. 19 In addition, Cys C has been shown to be a strong predictor of major adverse cardiovascular events and allcause mortality, [20][21][22] and the association between high levels of Cys C and any cause-related mortality is ageindependent. 18 Age is an established risk factor for both CKD and type 2 myocardial infarction (MI), especially in elderly patients.…”
Section: Introductionmentioning
confidence: 99%